KAJIAN PAKET PENGOLAAN TANAMAN TERPADU DAN PAKET PETANI PADI GOGO PADA DAERAH ALIRAN SUNGAI BATANG ASAI JAMBI - Syafri Edi; Defira Suci Gusfarina (Bioplantae, 2013)
Upland rice production is still low compared with the result of research and genetic potential. The low yield is caused by the use of cultivation technology that is not optimal and the limited of high yielding varieties cultivated that made many farmers still grow local rice for generations. High yielding varieties and Integrated Crop Management (ICM) technology is one of the reliable innovative technologies to increase the upland rice productivity. The study aims to determine the growth and production of upland rice with ICM technology package compared to farmer technology package. The experiment was conducted in the Batang Asai watershed, Panti Village, Sarolangun Jambi District. The study of ICM package and farmers package done by planting the two packages side by side on planting area of 1 ha each, consisting of four farmer cooperator, as well as for replicates. The research was done by using factorial design that compares the ICM package with farmers’ package through the t test. The results indicate that the ICM package provide a better growth and yield than the farmers package, such as the low intensity of leaf and neck blast disease and rice pest pests walang, positively impacted the percentage of grain pithy, weight of 1000 seeds and results. ICM package gives the highest yield 5216 kg/ha, while the farmer package 2,170 kg/ha, so there is an increase in the results of 3,046 kg/ha or 140.37%. Key words: Upland rice, integrated crop management